Pengaruh Ruang Fiskal, Pendapatan Asli Daerah, Dana Alokasi Umum, Persentase Pendududk Miskin, dan Rata-Rata Lama Sekolah Terhadap Belanja Pendidikan - Nur Rohmah Hidayati; Andy Dwi Bayu Bawono (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2020)
This research aims to examine the influence of fiscal space, locally generated revenue(PAD), general allocation funds (DAU), Proverty Rate (PPM), and Average Years School (RLS) on Education Expenditures. The population used in this study is all regency/city on Indonesia. The sampling method in this research using purposive sampling method, collected data processed 505 regency/city samples. The analysis used in this research is multiple linear regression analysis processed using the Statistical Package for Social Science (SPSS) version 21.00. The results of this study indicate that fiscal space, locally generated revenue (PAD), general allocation fund (DAU) affect education expenditures. While the average length of school (RLS) negatively influences education expenditure. The Percentage of Poor Population (PPM) has no effect on Education Expenditures